PGC 44685: A Dwarf Star-forming Lenticular Galaxy with a Wolf–Rayet Population - Shiying Lu; Qiusheng Gu; Yulong Gao; Yong Shi; Luwenjia Zhou; Rubén García-Benito; Xiangdong Li; Jiantong Cui; Xin Li; Liuze Long; Zhengyi Chen (The Astrophysical Journal, 2024)
Lenticular galaxies (S0s) are formed mainly from the gas stripping of spirals in the cluster. But how S0s form and evolve in the field is still in need of being resolved. Based on spatially resolved observations from the optical Hispanic Astronomical Center in Andalusia 3.5 m telescope with the PPAK Integral Field Spectroscopy instrument and Northern Extended Millimeter Array, we study a dwarf ( M _* < 10 ^9 M _⊙ ) S0, PGC 44685, with triple star-forming regions in the central region, namely, A, B, and C, respectively. In northwest region C, we clearly detect the spectral features of Wolf–Rayet (W-R) stars and quantify the W-R population by stacking spectra with high W-R significance. Most of the molecular gas is concentrated in region C(W-R), and there is diffuse gas around regions A and B. The W-R region possesses the strongest intensities of H α , CO(1–0), and 3 mm continuum, indicating its ongoing violent star formation (gas depletion timescale ≲25 Myr) with tentative hundreds (<500) km s ^−1 of stellar winds accompanied by the W-R phase. Most (∼96%) of the three star-forming regions show relatively low-metallicity distributions, suggesting possible (minor) accretions of metal-poor gas that trigger the subsequent complex star formation in a field S0 galaxy. We speculate that PGC 44685 will become quiescent in less than 30 Myr if there is no new molecular gas to provide raw materials for star formation. The existence of this dwarf star-forming S0 presents an example of star formation in the low-mass/metallicity S0 galaxy.